East Benue-Congo - Watters, John (My University, 2018)
Chapter one introduces this volume on East Benue-Congo (EBC) and the chapters addressing issues of nouns, pronouns, and verbs within specific branches and EBC as a whole. The chapter identifies the location of EBC and its branches as well as the external and internal classification of EBC. It situates EBC's likely original homeland and the geography of its probable expansion routes that led to the current location of its branches. It then provides a context for the chapters focused on noun classes in EBC in general and nominal affixes in Kainji and Plateau in particular, as well as the reconstruction issues they raise. It also notes certain issues related to Bantoid and to the presence of the Bantu languages within Bantoid, especially its dominance within Bantoid that has the potential of skewing historical analyses.
Keywords: East Benue-Congo; Nouns; Pronouns